Circular RNA is enriched and stable in exosomes： a promising biomarker for cancer diagnosis - Li, Yan; Zheng, Qiupeng; Bao, Chunyang; Li, Shuyi; Guo, Weijie; Zhao, Jiang; Chen, Di; Gu, Jianren; He, Xianghuo; Huang, Shenglin (Cell research, 2015)
Circular RNAs （circRNAs） are recently identified as a naturally occurring family of widespread and diverse endogenous noncoding RNAs that may regulate gene expression in mammals . They are unusually sta- ble RNA molecules with cell type- or developmental stage-specific expression patterns . Exosomes are small membrane vesicles of endocytic origin secreted by most cell types. They contain a specific cargo of protein, mRNA and microRNA species, which can modulate recipient cell behaviors and may be used as biomarkers for diagnosis of human diseases .